The Effect of EU Accession on the Hungarian Tobacco Sector. The Evaluation of the Regulations - Mislovics, Anita (Acta Agraria Debreceniensis, 2005)
Tobacco growing can be regarded as a special small sector of Hungarian agriculture. However, studying it from a different point of view, we can see that it is an outstanding sector among others in agriculture. Not only is its budget importance that makes it significant (its total budgetary income is more than 200 billion HUF), and on the other hand it also plays an important role in employment and income output. Nevertheless questions of regulation arise, and especially those of its justification, methods and scope. Moreover, EU accession forces Hungary to redraw its regulatory statutes for legal harmonization. Below is a discussion of the impacts of this process, as well as of the domestic tobacco market itself.